The Influence of Physical Education Lesson Context and Teacher Behaviour on Student Physical Activity in Mexico (La influencia del contexto de la clase de Educación física y de los comportamientos docentes en la actividad física de los alumnos en México) - Gharib, Hoda; Galavíz, Karla; Lee, Rebecca E.; Safdie, Margarita; Tolentino, Lizbeth; Barquera, Símon; Lévesque, Lucie (Retos, 2015)
Abstract. Objective: To explore the influence of physical education (PE) lesson context and teacher behaviour on moderate-to-vigorous physical activity (MVPA) in Mexican children during PE class. Methods: Trained observers rated the physical activity intensity (lying down, sitting, standing, walking, vigorous movement) of 232 students from grades 3 to 5, PE lesson context (management, general knowledge, fitness knowledge, fitness, skill practice, game play, free play), and teacher behaviour (promoting fitness, demonstrating, instructing, observing, managing, other task) during PE class in 20 public elementary schools in Mexico City using the System for Observing Fitness Instruction Time (SOFIT). Regressions with backward elimination were conducted. Results: Class duration was on average 33.6 minutes (SD=7.9). Boys (M=14.8 min, SD=6.8) spent more time in MVPA than girls (M=12.6 min, SD=6.1; p